Subsidising carbon capture. Effects on energy prices and market shares in the power market - Finn Roar Aune; Gang Liu; Knut Einar Rosendahl; Eirik Lund Sagen (Statistics Norway, Research Department, 2009)
This paper examines how ambitious climate policies and subsidies to carbon capture may affect international energy prices and market shares in the power market. A detailed numerical model of the international energy markets is used. We first conclude that an ambitious climate policy alone will have substantial effects in the power market, with considerable growth in renewable power production and eventually use of carbon capture. Gas power production will also benefit from such a policy. Subsidising carbon capture and storage (CCS) will significantly accelerate the use of this technology. Nevertheless, total production of coal and gas power (with or without CCS) is only marginally increased, as the subsidy mainly leads to installation of CCS equipment on existing plants, reducing the efficiency from these plants. Consequently, electricity prices are almost unchanged, and the substantial growth in renewable power production is hardly affected by the subsidies to CCS.
Keywords: H23; Q40; Q54; 330; Energy markets; Climate policy; Carbon capture